A high-strength polysaccharide-MXene composite microsphere and preparation method thereof

Through the complexation of MXene with polysaccharide molecules, high-intensity polysaccharide-MXene composite microspheres are formed, which solves the problem of insufficient mechanical strength of polysaccharide media, and achieves fast and efficient biological macromolecule separation and stable separation media, suitable for biocatalysis and protein chromatography Separate fields.

CN113368792BActive Publication Date: 2025-01-03CHINA UNIV OF PETROLEUM (EAST CHINA)
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202110683172.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-06-21
Publication Date
2025-01-03
Estimated Expiration
2041-06-21

AI Technical Summary

Technical Problem

The low mechanical strength of existing polysaccharide separation media limits the operating flow rate of biological macromolecules separation, leading to long separation time and inactivation of biological macromolecules.

Method used

MXene is used to complex with polysaccharide molecules, and high-strength polysaccharide-MXene composite microspheres are prepared by forming hydrogen bonds and subsequent chemical crosslinking to improve the mechanical strength and biocompatibility of the separation medium.

Benefits of technology

It significantly improves the separation speed and mechanical strength, extends the service life of the separation medium, ensures the stability of biological macromolecules and efficient separation and purification.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113368792B_ABST
    Figure CN113368792B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of preparation of natural polymer / inorganic nanosheet composite materials, and in particular to a high-strength polysaccharide-MXene composite microsphere and a preparation method thereof. The surface of MXene is rich in hydroxyl groups, and hydrogen bonds can be formed with the ‑OH / ‑O‑ and ‑O‑ / ‑OH on the polysaccharide molecular chain to play the role of additional physical crosslinking points, and then assisted by subsequent chemical crosslinking, high-strength polysaccharide-MXene composite microspheres are prepared. Protein adsorption and pressure flow rate curve experiments show that the composite microsphere has good biocompatibility, and the operating flow rate is greatly improved than that of simple polysaccharide microspheres. The composite microsphere has great application potential in the fields of biocatalysis and fast flow rate protein chromatography separation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of preparation of natural polymer / inorganic nanosheet composite materials, and in particular to a high-strength polysaccharide-MXene composite microsphere and a preparation method thereof. Background Art

[0002] In the fields of modern life technology such as medicine, artificial immunity and genetic diagnosis, the rapid and large-scale separation and preparation of biomacromolecules such as proteins, nucleic acids and viral vaccines is a bottleneck problem that needs to be solved urgently, because these biomacromolecules must be highly separated and purified before they can be used. Liquid chromatography technology has mild separation conditions and high resolution, and plays an irreplaceable role in the separation and purification of biomacromolecules. The quality of liquid chromatography separation performance depends on the performance of the separation medium. At present, the mainstream biomacromolecule separation medium is polysaccharide soft gel. The main reason is that this type of biological separation medium has good biocompatibility, large pore size allows biomacromolecules to pass through, and is rich in hydroxyl groups and easy to derive. However, the biggest problem of polysaccharide separation medium in use is poor mechanical strength, which can usually only be operated at low pressure (<0.3MPa), thereby limiting the operating flow rate. This will cause the biomacromolecules to contact the medium for a long time, which is easy to cause the inactivation of biomacromolecules with complex structures. Therefore, developing a separation medium with high column efficiency, large separation capacity, fast separation speed and good biocompatibility is the key to achieving large-scale separation and preparation of biomacromolecules.

[0003] Organic-inorganic composite materials can have the advantages of both organic and inorganic components, greatly expanding the application range of materials (European Polymer Journal, 2008, 44, 3271-3279), and have been a research hotspot in the field of materials in recent years. MXene is a new type of two-dimensional crystalline material similar to graphene. It is a titanium carbide or carbonitride. The precursor material of MXene is a ternary layered compound MAX phase, which can be peeled off by chemical etching (such as hydrofluoric acid) to obtain a two-dimensional MXene compound. MXene has attracted widespread attention in the field of electrochemical materials such as supercapacitors due to its electrical conductivity, thermal conductivity and excellent mechanical properties. In addition, MXene has excellent dispersibility in aqueous solution and can be used as an ideal nanomaterial to enhance the mechanical strength of composite materials. It has been reported in the literature (ACS Applied Materials & Interfaces, 2019, 11: 47350-47357) that adding a very small amount of MXene can effectively improve the mechanical strength and thermal stability of the polymer poly (N-isopropylacrylamide)-MXene composite hydrogel, thus confirming the potential of the composite hydrogel as an intelligent compression sensor. Summary of the invention

[0004] In view of the shortcomings of the current polysaccharide separation medium, such as low mechanical strength, only being able to operate at low flow rates, resulting in long separation time, thus causing inactivation of biomacromolecules and difficulty in large-scale separation and preparation of proteins, the present invention uses MXene and polysaccharide molecules for compounding. The -OH / -O- on the surface of MXene can form hydrogen bonds with the -O- / -OH on the polysaccharide molecular chain, acting as additional physical cross-linking points, and with the assistance of subsequent simple chemical cross-linking, high-strength polysaccharide-MXene composite microspheres are prepared. The composite microspheres have great application potential in the fields of biocatalysis and fast-flow protein chromatography separation. The reaction is schematically shown as follows:

[0005]

[0006] The technical solution adopted by the present invention is:

[0007] A method for preparing high-strength polysaccharide-MXene composite microspheres comprises the following steps:

[0008] (1) A certain volume of MXene dispersion is added to the polysaccharide aqueous solution, and the two are mixed evenly to form a dispersed water phase; an emulsifier and a water-insoluble organic solvent are mixed evenly to form a continuous oil phase. The water phase is dispersed into the oil phase under mechanical stirring, and a stable water-in-oil (W / O) emulsion is formed after emulsification for a certain period of time.

[0009] (2) Add a mixture of a chemical crosslinking agent and a catalyst to the above emulsion, carry out a chemical crosslinking reaction at a certain temperature, and after a period of reaction, wash the microspheres with cyclohexane, ethanol and deionized water in turn to obtain polysaccharide-MXene composite microspheres.

[0010] The polysaccharide in step (1) is selected from one of dextran, cellulose, konjac glucomannan and agarose. The preparation conditions of different polysaccharide aqueous solutions are different: dextran can be dissolved in water at room temperature; agarose needs to be heated to dissolve; konjac glucomannan needs to be first degraded with acid and then dissolved with alkali solution to obtain an aqueous solution (Preparation of beaded konjac glucomannan microspheres, master's thesis of Beijing University of Chemical Technology, 2007); cellulose aqueous solution can be dissolved by ionic liquid or sodium hydroxide-urea-water system. The concentration of the polysaccharide solution is 0.1-30% (w / w), preferably 2-10% (w / w).

[0011] The oil phase in step (1) can be selected from engine oil, vegetable oil, vacuum pump oil, kerosene, olive oil, liquid paraffin, petroleum ether, cyclohexane, halogenated hydrocarbons, such as dichloroethane, dichloromethane, chloroform, etc., aromatic compounds and halogenated compounds thereof, such as chlorobenzene, toluene, xylene, etc. One or a mixture of at least two of the above substances can be used as a solvent, for example, any combination of liquid paraffin / petroleum ether, carbon tetrachloride, dichloroethane / xylene / cyclohexane, etc. can be used as the oil phase.

[0012] MXene in step (1) is a new type of two-dimensional material with a graphene-like structure, and its chemical formula is M n+ 1X n T x , where n = 1, 2, 3, M is a pre-transition element (such as Ti, Sc, Zr, Nb, etc.), X is carbon or nitrogen, T x The surface functional groups (such as -OH, -O-, -F) of MXene are MAX phases, which are ternary layered compounds with the chemical formula M n+1 AX n , where M, X, and n are the same as above, and A is a III or IV main group element. Currently, more than 20 kinds of MXene have been prepared by etching methods. The preparation and addition concentration of MXene dispersion are key steps of the present invention: uneven dispersion of MXene will lead to its agglomeration in the polysaccharide microspheres, affecting the physical cross-linking effect and resulting in unsatisfactory mechanical strength of the composite microspheres. In the present invention, a homogenizer is used to prepare MXene dispersion; if the MXene concentration is too small, the mechanical strength of the composite microspheres is insufficient, and if the concentration is too high, the porosity of the composite microspheres will be reduced. The amount of MXene added is 0.1-20% of the mass of the polysaccharide, preferably 1-5%.

[0013] The emulsifier described in step (1) is selected from one or a mixture of at least two of the following: Span emulsifiers, cellulose emulsifiers, Tween emulsifiers, PO-500, Alarcel 83, and the concentration of the oil phase emulsifier is 0.5-10% of the mass of the oil phase solvent.

[0014] The volume ratio of the water phase to the oil phase in step (1) is 1:2-1:30, usually 1:(2-5); the operating temperature is 20-90°C; the mechanical stirring speed is 100-1500rpm; and the emulsification time is 10-100min.

[0015] There are many types of chemical crosslinking agents that can be used in step (2). Any substance having two or more groups that can react with hydroxyl groups can be used as a crosslinking agent, such as glutaraldehyde, glyoxal, epichlorohydrin, 1,4-butanediol diglycidyl ether, ethylene glycol diglycidyl ether, a monoepoxy or polyepoxy compound, and a mixture of one or at least two multifunctional compounds such as active halogen compounds. Any combination of the above substances can be used as the crosslinking agent of the present invention. The amount of the crosslinking agent used accounts for 15-50% of the volume of the aqueous phase.

[0016] The catalyst in step (2) refers to a base or an acid. The catalyst used in the aldehyde crosslinking agent is an acid, which can be selected from at least one of hydrochloric acid, nitric acid, sulfuric acid, acetic acid or a mixture thereof, and is added to ensure that the final aqueous phase acid concentration is within the range of 10 -4 -10 -1mM; the catalyst used for cross-linking agents such as glycidyl ethers, monoepoxy or polyepoxy compounds and active halogen compounds is a base, which can be selected from at least one of potassium hydroxide, sodium hydroxide, lithium hydroxide or a mixture thereof, and after addition, the final aqueous phase base concentration is ensured to be in the range of 0.5-10M.

[0017] In step (2), the crosslinking temperature is 10-80° C. The crosslinking reaction time is 0.5-24 h. After the reaction is completed, the polysaccharide-MXene composite microspheres can be obtained by washing and filtering multiple times.

[0018] Through the above steps, high-strength polysaccharide-MXene composite microspheres with an average particle size range of 10-200 μm and a skeleton of a polysaccharide polymer and MXene composite are finally obtained.

[0019] The present invention is beneficial in that:

[0020] The present invention utilizes the intermolecular hydrogen bonds formed by the functional groups (-OH, -O-) on the MXene and polysaccharide polymer chains during the composite process, so that the doped MXene acts as an additional physical crosslinking point, and then chemical crosslinking is used to obtain polysaccharide-MXene composite microspheres by reverse suspension polymerization. MXene can be purchased directly or made in the laboratory according to the method in the literature (ACS Applied Materials & Interfaces, 2019, 11: 47350-47357). Compared with the existing commercial polysaccharide microspheres, the surface structure of the polysaccharide-MXene composite microspheres of the present invention is uniform, the mechanical strength of the skeleton is significantly improved, and the operating flow rate after column loading is much higher than that of the commercial polysaccharide microspheres, which improves the separation speed. After further derivation, the composite microspheres have a wide range of applications in cell culture, enzyme immobilization, and rapid separation and purification of biomacromolecules. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 Optical microscope photograph of the dextran-MXene composite microspheres in Example 1;

[0022] Figure 2 Pressure-flow rate curves of the dextran microspheres after column loading in Example 1 and Comparative Example. Specific implementation methods

[0023] The specific implementation method of the present invention is as follows:

[0024] Embodiment 1:

[0025] 1) First weigh dextran T40 (7.5g) and dissolve it in 20ml ultrapure water, then weigh MXene (0.15g) and add it to 5ml deionized water, and disperse it evenly with a handheld homogenizer. Finally, add the dextran solution and MXene dispersion into a 50ml beaker and stir it evenly with a magnetic stirrer. In a 250ml three-necked flask equipped with a mechanical stirrer, add chlorobenzene (75ml) and Span 80 (2.4g) and heat it to 30℃ as the oil phase. Add the above-prepared water phase to the oil phase and emulsify it at 150rpm for 30min to obtain a gray W / O type emulsion.

[0026] 2) Slowly drop 5 ml of a mixed solution of crosslinking agent glutaraldehyde and 0.75 ml of concentrated hydrochloric acid into the above emulsion, and further perform a crosslinking reaction at 30°C. After reacting for 12 hours, wash the microspheres with cyclohexane, ethanol and deionized water in turn to obtain dextran-MXene composite microspheres with an average particle size of 90 μm. The crosslinked composite microspheres are stored in 20% ethanol at 4°C.

[0027] Embodiment 2:

[0028] 1) First, weigh agarose (0.6 g) and 10 ml ultrapure water into a 100 ml round-bottom flask, and heat with magnetic stirring at 90 ° C until the solution is clear and transparent. Then weigh MXene (0.06 g) and add it to 5 ml deionized water. Use a handheld homogenizer to disperse it evenly. Finally, mix the MXene dispersion and agarose solution evenly as the water phase. In a 250 ml three-necked flask equipped with a mechanical stirrer, add liquid paraffin (70 ml), petroleum ether (30 ml), Span 80 (3.6 g) and Tween (0.4 g) and heat to 70 ° C as the oil phase. Add the above-prepared water phase to the oil phase and emulsify for 30 minutes at 400 rpm to obtain a gray W / O type emulsion.

[0029] 2) Slowly drop 4 ml of a mixed solution of crosslinker ethylene glycol diglycidyl ether and 2 ml of 50% KOH into the above emulsion, and further crosslink at 70°C. After 8 hours of reaction, the microspheres are washed with cyclohexane, ethanol and deionized water in turn to obtain agarose-MXene composite microspheres with an average particle size of 65 μm. The crosslinked composite microspheres are stored in 20% ethanol at 4°C.

[0030] Embodiment 3:

[0031] 1) First, weigh cellulose (1.0 g) and 20 ml of cellulose solution (sodium hydroxide: urea: water = 7:12:81) ultrapure water into a 100 ml round-bottom flask as the water phase, and heat with magnetic stirring at 90 ° C until the solution is clear and transparent. Then weigh MXene (0.05 g) and add it to 5 ml of deionized water, and disperse it evenly with a handheld homogenizer. Finally, mix the MXene dispersion and cellulose solution evenly as the water phase. In a 250 ml three-necked flask equipped with a mechanical stirrer, add olive oil (100 ml) and hydroxyethyl cellulose (4 g) and heat to 90 ° C as the oil phase. Add the above-prepared water phase to the oil phase and emulsify for 50 minutes at 1000 rpm to obtain a gray W / O type emulsion.

[0032] 2) Slowly add 6 ml of a mixed solution of crosslinker 1,4-butanediol diglycidyl ether and 2 ml of 40% NaOH to the above emulsion, and further carry out crosslinking reaction at 70°C. After reacting for 12 hours, wash the microspheres with cyclohexane, ethanol and deionized water in turn to obtain cellulose-MXene composite microspheres with an average particle size of 45 μm. After crosslinking, the composite microspheres are stored in 20% ethanol at 4°C.

[0033] Embodiment 4:

[0034] 1) Reference method (Konjac glucomannan microspheres of uniform size and preparation method thereof, invention patent number ZL 201110387111.9) A 4% konjac glucomannan aqueous solution was prepared: 4 g of konjac flour was weighed and placed in a single-necked flask containing 10 ml of 0.5 M HCl and 60 ml of deionized water, stirred evenly and placed in an oven at 115 ° C for 30 min, cooled and added with 30 ml of 40% NaOH solution, stirred to dissolve the slurry, and filtered to obtain a 4% konjac glucomannan solution.

[0035] 2) Weigh MXene (0.02 g) and add it to 5 ml of deionized water. Use a handheld homogenizer to disperse it evenly. Finally, mix the MXene dispersion with 20 ml of the above konjac glucomannan solution and use it as the water phase. In a 250 ml three-necked flask equipped with a mechanical stirrer, add liquid paraffin (75 ml), Span 80 (2 g) and PO500 (2 g) and heat to 40 ° C as the oil phase. Add the prepared water phase to the oil phase and emulsify for 30 min at 300 rpm to obtain a gray W / O emulsion.

[0036] 3) Slowly add 5 ml of epichlorohydrin to the above emulsion, further cross-linking reaction at 40°C, and wash the microspheres with cyclohexane, ethanol and deionized water in turn after 12 hours to obtain konjac glucomannan-MXene composite microspheres with an average particle size of 123 μm. The cross-linked composite microspheres are stored in 20% ethanol at 4°C.

[0037] Comparative Example 1:

[0038] 1) Weigh dextran T40 (7.5 g) and 25 ml ultrapure water into a 100 ml round-bottom flask as the water phase and stir magnetically until the solution is clear and transparent. In a 250 ml three-necked flask equipped with a mechanical stirrer, add chlorobenzene (75 ml) and Span 80 (2.4 g) and heat to 30°C as the oil phase. Add the prepared water phase into the oil phase and emulsify at 150 rpm for 30 min to obtain a white W / O emulsion.

[0039] 2) Slowly drop 5 ml of a mixed solution of crosslinking agent epichlorohydrin and 2.5 ml of 50% NaOH into the above emulsion, and further perform crosslinking reaction at 30°C. After reacting for 12 hours, wash the microspheres with cyclohexane, ethanol and deionized water in turn to obtain dextran microspheres with an average particle size of 89 μm. The crosslinked composite microspheres are stored in 20% ethanol at 4°C.

[0040] Comparative Example 2:

[0041] 1) Weigh dextran (0.75 g), lithiasis earth (0.15 g) and 25 ml ultrapure water into a 100 ml round-bottom flask as the water phase, and stir evenly with a magnetic stirrer until the solution is clear and transparent. In a 250 ml three-necked flask equipped with a mechanical stirrer, add chlorobenzene (75 ml) and Span 80 (2.4 g) and heat to 30°C as the oil phase. Add the prepared water phase into the oil phase and emulsify at 150 rpm for 30 min to obtain a white W / O type emulsion.

[0042] 2) Slowly drop 5 ml of a mixed solution of crosslinking agent epichlorohydrin and 2.5 ml of 50% NaOH into the above emulsion, and further perform crosslinking reaction at 30°C. After reacting for 12 hours, wash the microspheres with cyclohexane, ethanol and deionized water in turn to obtain dextran-lithium lava composite microspheres with an average particle size of 85 μm. After crosslinking, the composite microspheres are stored in 20% ethanol at 4°C.

[0043] Effect experiment:

[0044] In order to verify the mechanical strength and biocompatibility of the polysaccharide-MXene composite microspheres of the present invention, the adsorption of bovine serum albumin (BSA) by the dextran-MXene composite microspheres prepared in Example 1 was compared with the dextran microspheres and dextran-lithium tantalum composite microspheres (preliminary preparation in the laboratory) prepared in the comparative example. At the same time, the above-mentioned microspheres were loaded into a column, a 150×4.6mm ID stainless steel column, and the mobile phase was ultrapure water, and its pressure flow rate curve was measured.

[0045] After the microspheres were loaded into the column, the back pressure of the dextran white sphere without MXene in the comparative example increased sharply when the flow rate reached 1083 cm / h, indicating that the medium was compressed and deformed at this time and could no longer be operated. The back pressure of the dextran-lithium lava composite microspheres was 1.38 MPa at the maximum flow rate of 3610 cm / h. The pressure-flow curve of the dextran-MXene composite microspheres prepared in Example 1 was still in a good linear relationship when the system had a maximum flow rate of 3610 cm / h, and the back pressure was 0.85 MPa (see Appendix). Figure 2 ), indicating that the addition of Mxene not only significantly improves the mechanical strength of the composite microspheres, but also improves the bed permeability. In pH 7.0 phosphate buffer at 25°C, the adsorption of bovine serum albumin (BSA) by different microspheres is shown in Table 1.

[0046] Table 1 Comparison of the adsorption of bovine serum albumin (BSA) by dextran-MXene composite microspheres in Example 1 and dextran white microspheres in the comparative example

[0047]

[0048] The results show that at pH 7.0 and 25°C, the adsorption of BSA by the prepared dextran-MXene composite microspheres is comparable to that of dextran white spheres, and slightly lower than that of dextran-lithium lava composite microspheres, indicating that the addition of MXene does not change the good biocompatibility of dextran microspheres. In other words, the polysaccharide-MXene composite microspheres prepared by the present invention still have the good biocompatibility of polysaccharides, and the mechanical strength is greatly improved, and are a very potential fast flow protein chromatography matrix.

Claims

1. A method for preparing high-strength polysaccharide-MXene composite microspheres, characterized in that the steps include: (1) A certain volume of MXene dispersion is added to the polysaccharide aqueous solution, and the two are mixed evenly as the dispersed water phase. The emulsifier and the water-insoluble organic solvent are mixed evenly as the oil phase, and the oil phase is used as the continuous phase; the water phase is dispersed into the oil phase under mechanical stirring conditions, and a stable water-in-oil (W / O) emulsion is formed after emulsification for a certain period of time; (2) Add a mixture of a chemical crosslinking agent and a catalyst to the above emulsion, carry out a chemical crosslinking reaction at a certain temperature, and wash the microspheres with cyclohexane, ethanol and deionized water in turn after a period of reaction to obtain polysaccharide-MXene composite microspheres; the chemical crosslinking agent is a substance having two or more groups that can react with hydroxyl groups.

2. The method for preparing high-strength polysaccharide-MXene composite microspheres according to claim 1, characterized in that: The polysaccharide described in step (1) is at least one of dextran, cellulose, konjac glucomannan and agarose.

3. The method for preparing high-strength polysaccharide-MXene composite microspheres according to claim 1, characterized in that: The oil phase in step (1) is selected from one or a mixture of at least two of engine oil, vegetable oil, vacuum pump oil, kerosene, liquid paraffin, olive oil, petroleum ether, cyclohexane, dichloroethane, dichloromethane, chloroform, carbon tetrachloride, chlorobenzene, toluene and xylene as solvent.

4. The method for preparing high-strength polysaccharide-MXene composite microspheres according to claim 1, characterized in that: The oil phase emulsifier described in step (1) is selected from one or a mixture of at least two of the following: Span emulsifiers, cellulose emulsifiers, Tween emulsifiers, PO-500, Alarcel83, and the concentration of the oil phase emulsifier is 0.5-10% based on the mass of the oil phase.

5. The method for preparing high-strength polysaccharide-MXene composite microspheres according to claim 1, characterized in that: The amount of MXene added in step (1) is 0.1-20% based on the mass of the polysaccharide.

6. The method for preparing high-strength polysaccharide-MXene composite microspheres according to claim 1, characterized in that: In step (1), the volume ratio of the water phase to the oil phase is 1:2-1:30; the operating temperature is 20-90° C.; the mechanical stirring speed is 100-1500 rpm; The emulsification time is 10-100min.

7. The method for preparing high-strength polysaccharide-MXene composite microspheres according to claim 1, characterized in that: The chemical crosslinking agent described in step (2) is selected from glutaraldehyde, glyoxal, epichlorohydrin, 1,4-butanediol diglycidyl ether, ethylene glycol diglycidyl ether, a monoepoxy or polyepoxy compound, and a mixture of one or at least two of a polyfunctional compound containing an active halogen compound; the crosslinking agent accounts for 15-50% of the volume of the aqueous phase.

8. The method for preparing high-strength polysaccharide-MXene composite microspheres according to claim 7, characterized in that: The catalyst described in step (2) refers to a base or an acid; wherein the catalyst used for the aldehyde crosslinking agent is an acid, and at least one of hydrochloric acid, nitric acid, sulfuric acid, and acetic acid is selected, and after addition, the final aqueous phase acid concentration is ensured to be within the range of 10 -4 -10 -1 mM; the catalyst used for glycidyl ethers, monoepoxy or polyepoxy compounds and cross-linking agents containing active halogen compounds is a base, selected from at least one of potassium hydroxide, sodium hydroxide and lithium hydroxide, and after addition, the final aqueous phase base concentration is ensured to be in the range of 0.5-10M.

9. The method for preparing high-strength polysaccharide-MXene composite microspheres according to claim 1, characterized in that: In step (2), the cross-linking temperature is 10-80° C. and the cross-linking reaction time is 0.5-24 h.

10. A polysaccharide-MXene composite microsphere obtained by the method of claim 1, characterized in that The skeleton of the microsphere is composed of a composite of polysaccharide polymer and MXene, and the average particle size ranges from 10 to 200 μm.

Citation Information

Patent Citations

  • Konjac glucomannan microballoon with uniform dimension and preparation method thereof

    CN102492178A

  • Cellulose / two-dimensional layered material composite hydrogel and preparation method thereof

    CN107973920A

  • High-strength polysaccharide-nano-laponite composite microsphere and preparation method thereof

    CN110935406A